2011
DOI: 10.3141/2250-07
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lighted Pavement Marker Stop Bars at Intersections with Light Rail Lines

Abstract: This paper presents an evaluation of the use of lighted pavement markers parallel to an intersection stop bar for three treatment intersections in Houston, Texas. The line of pavement markers was active, with a red light displayed from each marker during the red interval of the traffic signal. Each lighted pavement marker contained multiple LEDs, which operated such that each marker displayed an alternating wigwag pattern. The intended impact of the pavement markers was to reduce red light running violations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The effectiveness of countdown timers on red light running has also been evaluated in several other studies where potential decrease in RLVs was reported (Chiou & Chang, 2010;Kidwai et al, 2005;Limanond et al, 2010;Lum & Halim, 2006;Rijavec et al, 2013). Tydlacka et al (2011) investigated the effectiveness of lighted stop bar system (LSBS) installed parallel to the intersection stop line for three intersections in Houston, Texas. The LSBS containing red LED light units was operated in a steady burn mode during the red interval while it was deactivated during the yellow and green intervals.…”
Section: Field Observation Studiesmentioning
confidence: 99%
“…The effectiveness of countdown timers on red light running has also been evaluated in several other studies where potential decrease in RLVs was reported (Chiou & Chang, 2010;Kidwai et al, 2005;Limanond et al, 2010;Lum & Halim, 2006;Rijavec et al, 2013). Tydlacka et al (2011) investigated the effectiveness of lighted stop bar system (LSBS) installed parallel to the intersection stop line for three intersections in Houston, Texas. The LSBS containing red LED light units was operated in a steady burn mode during the red interval while it was deactivated during the yellow and green intervals.…”
Section: Field Observation Studiesmentioning
confidence: 99%
“…A similar approach in Dublin to improve the awareness of road-vehicle drivers is presented in Figure 8, d and e. Flashing red road studs (to display with a red traffic signal; indicated by arrows) were provided in a junction after analysis indicated that the main cause of road traffic collisions there was the failure of vehicles to stop at the red traffic signal. The effectiveness of this solution in Houston, Texas, to avoid red-light running at LRT intersections was discussed by Tydlacka et al (15).…”
Section: Intersectionsmentioning
confidence: 99%